2018
DOI: 10.1007/s00381-018-3925-4
|View full text |Cite
|
Sign up to set email alerts
|

Papillary craniopharyngioma in a 4-year-old girl with BRAF V600E mutation: a case report and review of the literature

Abstract: Introduction Craniopharyngiomas are one of the most frequently diagnosed hypothalamo-pituitary tumors in childhood. The adamantinomatous histological subtype accounts for most pediatric cases, while the papillary variant is almost exclusively diagnosed in adults. Here, we report a case of papillary craniopharyngioma in a very young child, confirmed by molecular tissue analysis. Case report A 4-year-old girl was being investigated for symptomatic central hypothyroidism. Brain MR imaging revealed a large solid/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Childhood-onset CP histology was exclusively adamantinomatous. pCP is described in children, but it is extremely rare [35]. In adult-onset CP, pCP was histologically confirmed in 40%, concordant with the previous reports, recognizing this subtype in 14-50% of adult-onset CP [36].…”
Section: Discussionsupporting
confidence: 86%
“…Childhood-onset CP histology was exclusively adamantinomatous. pCP is described in children, but it is extremely rare [35]. In adult-onset CP, pCP was histologically confirmed in 40%, concordant with the previous reports, recognizing this subtype in 14-50% of adult-onset CP [36].…”
Section: Discussionsupporting
confidence: 86%
“…Brastianos et al (13) recently reported on impressive tumor reduction in a pCP patient with BRAFV600E mutation treated with a combination therapy of a BRAF inhibitor (dabrafenib) and a MEK inhibitor (trametinib). A rare case of a pediatric pCP patient presenting with a BRAF V600E mutation was recently reported by Borrill et al (14). Another rare case of pediatric pCP with potential transition of Rathke cleft cyst metaplasia to pCP was recently published by Schlaffer el al.…”
Section: Papillary Craniopharyngioma (Pcp)mentioning
confidence: 93%
“…It has been hypothesized that PCP may arise from RCC by acquiring a BRAF (B-Raf proto-oncogene, serine/threonine kinase) mutation as the presence of squamous metaplasia in RCC has been associated with increased recurrence, which may reflect a continuum between RCCs and PCPs. 2,[5][6][7] Our case of PCP may possibly have had components of RCC or remnants.…”
mentioning
confidence: 87%
“…3 While ACPs are more common and have a bimodal age distribution with most cases seen in children and older adults, 4 PCPs are seen almost exclusively in adults. 2,4,5 ACPs are characterized by ameloblastoma-like epithelium with peripheral palisading, stellate reticulum admixed with wet keratin, and occasional calcifications and xanthomatous change. 2,6 The majority of ACPs show mutations in the CTNNB1 gene leading to the translocation of β-catenin protein from the membrane to the nucleus that can be demonstrated on immunohistochemistry.…”
mentioning
confidence: 99%
See 1 more Smart Citation